To believe or not to believe: Assessing the credibility of social media as non-formal learning - Ralf St. Clair; Maryam Shirdel Pour Ms; James Nahachewsky (Adult Education Research Conference, 2023)
Examines the criteria used by adults to assess the credibility of resources encountered online and the extent to which they differ from younger cohorts. Key information for design of adult online education.
Keywords: online education; credibility; engagement; adult learning